2017
DOI: 10.1097/prs.0000000000002936
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Wait Time and Treatment of Traumatic Digit Amputation: Do Race and Insurance Matter?

Abstract: Background Little is known about the association between the quality of trauma care and management of non-fatal injuries. We used emergency department (ED) wait times as a proxy for hospital structure, process, and availability of on-call surgeons with microsurgical skills. We evaluated the association between average hospital ED wait times and likelihood of undergoing digit replantation for patients with traumatic amputation digit injuries. We hypothesized that hospitals with shorter ED wait times were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…27,28 Furthermore, a 2017 study of emergency department wait times showed that patients with public or no insurance experienced longer wait times, which were associated with lower odds of replantation. 29 These results indicate that a surgeon’s financial incentives may influence surgical decision making, but we also need to consider that patients with a lower socioeconomic status are more likely to have public insurance and thus elect to undergo a revision amputation procedure that costs less and requires shorter recovery, so that they can return to work quickly. 22 In other words, patients with limited financial resources may forego a recommended treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Furthermore, a 2017 study of emergency department wait times showed that patients with public or no insurance experienced longer wait times, which were associated with lower odds of replantation. 29 These results indicate that a surgeon’s financial incentives may influence surgical decision making, but we also need to consider that patients with a lower socioeconomic status are more likely to have public insurance and thus elect to undergo a revision amputation procedure that costs less and requires shorter recovery, so that they can return to work quickly. 22 In other words, patients with limited financial resources may forego a recommended treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…For example, having no insurance was associated with longer emergency department wait times. 26 In addition, many health insurance plans impose a limit on the number of occupational therapy or physical therapy visits allowed per diagnosis per year and may also limit the duration of an episode of care. Patients in this situation are prone to rationing their therapy visits, which leads to poorer health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…24 Last, race can influence logistical access to care for patients, such that being a minority is associated with longer emergency department wait times. 26…”
Section: Discussionmentioning
confidence: 99%
“…Microsurgery training is part of the medical residency programs syllabus for hand surgery specialization. 20 21 22 23 24 25 26 27 However, we must ask ourselves if this training is enough for a good practice and if the substrate given to the physician during training is sufficient for the proper, safe performance of such procedures after graduation.…”
Section: Discussionmentioning
confidence: 99%
“…O treinamento em microcirurgia faz parte da grade curricular nos programas de residência médica para a especialidade de cirurgia da mão. 20 21 22 23 24 25 26 27 Porém, ainda é um questionamento que devemos fazer se este treinamento é suficiente para uma boa prática e se o substrato que foi dado ao médico durante sua formação lhe dá aptidão e segurança suficientes para realizar todos os procedimentos após o término da graduação.…”
Section: Discussionunclassified